The effects of coding on children's planning and inhibition skills. (April 2020) - Arfé, Barbara; Vardanega, Tullio; Ronconi, Lucia
Abstract: Computational thinking (CT) and the coding element of it are progressively entering in the primary school curriculum worldwide. Yet, little is known about the effects of these skills on children's cognitive development. In a cluster-randomized controlled trial, we examined how 1st-grade children's gains in coding skills that follow instructional intervention transfer to two important executive functions (EFs): planning and response inhibition. One-hundred seventy-nine (179) first graders from 5 schools and 10 class groups, with no prior experience of coding, were randomly assigned to an experimental (coding, 5 classes) or control (standard STEM, 5 classes) instructional condition. The experimental intervention involved 8 h of coding activities (two weekly lessons for 4 weeks), through the Code.org platform. Children in the control group were exposed to standard STEM instruction. Four coding tasks drawn from Code.org, two standardized planning tasks (Elithorn maze test and Tower of London, ToL, test) and two standardized response inhibition tasks (NEPSY-II inhibition subtest and numerical Stroop), were used to assess children's skills at the pretest and posttest (after the instructional intervention). To measure retention, the same skills were also assessed for 44 children from the experimental group 5 weeks from the posttest (follow up). The results show that practice with coding through Code.org not only improved measurably children's ability to solve coding problems, but also their EFs, increasing the time children spent planning, their ability to solve standardized planning tasks, and to inhibit prepotent responses. Such findings add to the still limited literature on the cognitive effects of coding, deepening our understanding of the positive implications of introducing Computational Thinking early in the school curriculum. Highlights: Eight hours practice with Code.org are sufficient to support the development of coding skills in 6-year old children. Gains in coding skills are transferred to children's executive functions: planning and response inhibition. Transfer of coding effects is more evident for planning than for response inhibition. The use of different cognitive tasks to assess the degree of cognitive transfer is important.